Study of structural, electrical, and optical properties of MoRe₀.₀₀₁Se₁.₉₉₉ single crystal - Vora, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
In the present work, structural, electrical, and optical properties of MoRe₀.₀₀₁Se₁.₉₉₉ single crystal grown using the direct vapour transport (DVT) method have been reported. The crystal has been structurally characterized by XRD, determining its lattice parameters and , and by measuring the X-ray density. The obtained data of the Hall effect and thermoelectric power measurements support that this crystal is of -type in nature. The direct and indirect band gap measurements were also carried out for this semiconducting material. It has been ascertained that the rhenium doping has a considerable effect on the properties of the MoSe₂ single crystal. У цій роботі повідомлено про структурні, електричні та оптичні властивості монокристала MoRe₀.₀₀₁Se₁.₉₉₉, вирощеного методом прямого перенесення пари. Структуру кристала проаналізовано методом рентгенівської дифракції, визначено його параметри решітки і та виміряно рентгенівську густину. Отримані дані з вимірювання ефекту Холла та термоелектричної потужності підтверджують, що цей кристал є -типу. Для цього напівпровідного матеріалу також проводилися прямі та непрямі вимірювання забороненої зони. Було встановлено, що легування ренієм значно впливає на властивості монокристала MoSe₂.